The Birth of Science - Kossovsky, Alex Ely.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book reveals the multi-generational process involved in the discovery of modern physics and examines the personal lives of six of the intellectual giants involved. It explores the profound revolution in the way of thinking, and in particular the successful refutation of the school of thought inherited from the Greeks, which focused on the perfection and immutability of the celestial world. In addition, the emergence of the scientific method and the adoption of mathematics as the central tool in scientific endeavors are discussed. Lastly, the book turns to Kepler's crucial 3rd law and shows how it was derived from a mere six data points, corresponding to the six planets known at the time. Written in a straightforward and accessible style, the book will inform and fascinate all aficionados of science, history, philosophy, and, in particular, astronomy.
Chapter 1 - The Scholars Who Sequentially Ignited the Scientific Revolution -- Chapter 2 - Was it an Apple, Moon, or Planets for Newton? -- Chapter 3 - Galileo's Other Revolution -- Chapter 4 - Nicolaus Copernicus and the Heliocentric Model -- Chapter 5 - Tycho Brahe - The Meticulous Celestial Recorder -- Chapter 6 - Johannes Kepler - The First Data Analyst -- Chapter 7 - Kepler's Attempts to Fit Orbits Geometrically -- Chapter 8 - Kepler's 1st Law - Discovery of Elliptical Orbits -- Chapter 9 - Kepler's 2nd Law - Differentiated Orbital Speeds -- Chapter 10 - Kepler's 3nd Law - Harmony of the Planets -- Chapter 11 - Implication of the Third Law to Orbital Speed -- Chapter 12 - The Third Law is Independent of Planets' Mass -- Chapter 13 - Galileo Galilei - The Father of Science -- Chapter 14 - Galileo's Discoveries about Falling Bodies -- Chapter 15 - Rate of Fall is Independent of Body's Mass -- Chapter 16 - Galileo's Analysis of Projectile Motion.-Chapter 17 - Galileo's Hint at the Concept of the Vector -- Chapter 18 - Galileo's Puzzling Hint at Celestial Application -- Chapter 19 - Galileo's Discoveries about Pendulum Motion -- Chapter 20 - Galileo's Astronomical Discoveries -- Chapter 21 - Galileo's Trial and Imprisonment -- Chapter 22 - Galileo's Writings on Relativity and Infinities -- Chapter 23 - Galileo's Work on Sound and Speed of Light -- Chapter 24 - Rene Descartes - The Rationalist Mathematician -- Chapter 25 - Isaac Newton and the Birth of Modern Physics -- Chapter 26 - The Publication of Principia -- Chapter 27 - The Bitter Dispute with Leibniz over Calculus Priority -- Chapter 28 - The Scientific Split Between England and Continental Europe -- Chapter 29 - Newton's Later Years and Royal Mint Work.-Chapter 30 - Newton's Semi-Heretical Christian Beliefs -- Chapter 31 - Newton's Three Laws of Motion -- Chapter 32 - Newton's Law of Universal Gravitation -- Chapter 33 - Deriving Kepler's 3rd Law from Newton's Laws -- Chapter 34 - The Rationale behind the Gravitational Formula -- Chapter 35 - The Observer, the Organizer, and the Theorist -- Chapter 36 - The European Nationalities of the Six Scholars -- Chapter 37 - The Supposed Vocations of the Six Scholars.-Chapter 38 - A Tale of Two Laws - Bode's Law & Kepler Law.
Keywords: Astronomy; Astrophysics; Physics; History; Mathematics; Astronomy, Astrophysics and Cosmology; History and Philosophical Foundations of Physics; History of Science; Mathematics, general